Handbook of chemical industry labeling - O'Connor, Charles J.; Lirtzman, Sidney I., 1930-2017 (Noyes Publications, 1984)
This handbook has been designed to provide a review of, and to act as a source for, the major elements of a hazardous label communication program--to serve the needs of labor, industry, and the public.